Viewing L2 captioned videos: what's in it for the listener?. Issue 4 (4th May 2018) - Yeldham, Michael
ABSTRACT: Captioning is commonly used to scaffold video viewing for second language learners, with the captioning affording the learners access to authentic videos that would ordinarily be out of their reach. Ostensibly the videos are mainly shown to help improve the learners' listening abilities. However, there is the view that the learners largely tend to just read the captions at the expense of listening to the speakers, thus doing little more than improving their reading skills. Consequently, this article examines a number of past studies to investigate whether this is the case or whether the learners' listening may indeed benefit. A key approach to this investigation of the past research is to ascertain how the learners process the videos; there is obviously the need for the learners to listen, to some degree, for their listening abilities to develop. The investigation finds that less-proficient learners tend more to read texts than listen to them, while more-proficient learners generally utilize a wider range of cues (caption, speaker and visual), although various factors may mediate these trends. Based on these findings, pedagogical suggestions are made for classroom teachers' use of captioned videos, along with suggestions for the future research of captioned viewing.